Immediate effect of visual and auditory feedback to control the running mechanics of well-trained athletes - Eriksson, M.; Halvorsen, K. A.; Gullstrand, L. (Journal of Sports Sciences, 2011)
The correlation between mechanical factors of running and running economy as measured by metabolic cost is a subject of much interest in the study of locomotion. However, no change in running technique has been shown to result in an immediate improvement in running economy on an intra-individual basis. To evaluate the effect of a modified running technique, it is probably necessary that the individual trains with the new technique for a longer period using a feedback system to control the new kinematics. In this study, we examine the feasibility of using visual and auditory feedback to adapt running technique according to a simplistic model of the mechanical cost of running. The model considers only the mechanical work against gravity, which is the product of the magnitude of the vertical displacement of the runner's centre of mass and the step-frequency. In the experiments reported here, 18 trained runners, running at 16 km/h on a treadmill, were given feedback on these parameters together with indicated target levels. In almost all cases, the runners were able to adjust their technique accordingly.